Motivation of non-monogamous adults to engage in sex with their different partners - Kelberga (Kelberg), Anna; Martinsone, Baiba (Frontiers in Psychology, 2022)
This study compared motivations of individuals in non-monogamous relationships to engage in sex with their different partners (n = 596, out of which 103 non-consensual non-monogamous, 135 polyamorous, 204 swinging, 154 in open relationships; women—38.8%, men—59.7%, other gender—1.5%; age range: from 18 to 65+ years; 86% of respondents between 25 and 54 years old; majority of the respondents are in a long-term relationship). The research aim was to identify whether there are differences in reasons to engage in sex with respondents’ primary versus secondary partners. Presented with 17 reasons to engage in sexual activity, the respondents rated the frequency with which they engage in sex for each reason with their different partners. Questions for 14 reasons to engage in sex were created based on the YSEX? questionnaire (Meston & Buss, 2007) and three questions were created specifically for non-monogamous population. The three new questions addressed the desire for a specific type of sex (such as kink, fetish, etc.), desire to have sex with a partner of another gender than one’s primary partner, and desire to experience the thrill of the forbidden. The results indicated that there are significant differences in motivation to engage in sex with one’s primary versus secondary partner for most of the reasons. Additionally, this study investigated whether there are differences in motivation to engage in sex with different partners depending on the relationship arrangement. The data analysis shows that there are differences in reasons to engage in sex with one’s different partners between non-consensually and consensually non-monogamous groups. This research compliments existing body of research with new reasons to engage in sex, it demonstrates that non-monogamous people engage in sex with their different partners for different reasons and reveals that these may vary depending on the type of the relationship arrangement.